Competing priorities: lessons in engaging students to achieve energy savings in universities. Issue 7 (5th November 2018) - Bull, Richard; Romanowicz, Joanna; Jennings, Neil; Laskari, Marina; Stuart, Graeme; Everitt, Dave
Abstract : Purpose: This paper aims to present findings from an EU-funded international student-led energy saving competition (SAVES) on a scale previously unseen. There are multiple accounts of short-term projects and energy saving competitions encouraging pro-environmental behaviour change amongst students in university dormitories, but the purpose of this research is to provide evidence of consistent and sustained energy savings from student-led energy savings competitions, underpinned by practical action. Design/methodology/approach: A mixed-methods approach (pre- and post-intervention surveys, focus groups and analysis of energy meter data) was used to determine the level of energy savings and quantifiable behaviour change delivered by students across participating university dormitories. Findings: This research has provided further insight into the potential for savings and behaviour change in university dormitories through relatively simple actions. Whilst other interventions have shown greater savings, this project provided consistent savings over two years of 7 per cent across a large number of university dormitories in five countries through simple behaviour changes. Research limitations/implications: An energy dashboard displaying near a real-time leaderboard was added to the engagement in the second year of the project. Whilst students were optimistic about the role that energy dashboards could play, the evidence is not here to quantify the impact of dashboards. Further research is required to understand the potential of dashboards to contribute to behavioural change savings and in constructing competitions between people and dormitories that are known to each other. Social implications: SAVES provided engagement with students, enabling, empowering and motivating them to save energy – focusing specifically on the last stage of the "Awareness, Interest, Desire, Action" framework. Automated meter reading data was used in the majority of participating dormitories to run near real-time energy challenges through an energy dashboard that informed students how much energy they saved compared to a target, and encouraged peer-to-peer learning and international cooperation through a virtual twinning scheme. Originality/value: Findings from energy saving competitions in universities are typically from small-scale and short-term interventions. SAVES was an energy-saving competition in university dormitories facilitated by the UK National Union of Students in five countries reaching over 50, 000 students over two academic years (incorporating dormitories at 17 universities). As such it provides clear and important evidence of the real-world long-term potential efficiency savings of such interventions.